Short Communication: Water quality improvement of Nile tilapia and catfish polyculture in aquaponics system - ZAHIDAH HASAN; YAYAT DHAHIYAT; YULI ANDRIANI; IRFAN ZIDNI (Smujo International, 2017)
Hasan Z, Dhahiyat Y, Andriani Y, Zidni I. 2016. Water quality improvement of Nile tilapia and catfish polyculture in aquaponics system. Nusantara Bioscience 8: 83-85. Research on the improvement of polyculture water quality in aquaponics system was conducted from July 2014 to August 2014. This study aims to improve the water quality in Nile tilapia and catfish polyculture by applying the aquaponics system. The results show that several water quality parameters increase, such as dissolved oxygen, ammonia, and nitrate. Meanwhile, Orthophosphate tends to be similar both in aquaponics system and control. The study is conducted experimentally by using completely randomized design. The cultured fish are catfish and Nile tilapia while the aquatic plants are water spinach and lettuce. At the end of the study the concentration of dissolved oxygen in the aquaponics system ranges from 5.3 to 7.6 mg/L, while in the media control ranges from 4.2 to 4.3 mg/L. Average concentrations of ammonia, nitrate and orthophosphate in the aquaponics system range from 0.003 to 0.25 mg/L, 10.0 to 50.7 mg/L and 3.0 mg/L-5.0 mg/L respectively. Meanwhile, in media control, concentration of those three parameters are 0.003 to 0.35 mg/L, 10.0 to 60.0 mg/L and 3.0 to 5.0 mg/L respectively. Based on this study, it is concluded that the polyculture water quality can be improved through the application of the aquaponics system.